The Role Of Spouse In Caring For Couples Suffering From Mental Disorders in the Balen Public Health Center - Putri, Evita Muslima Isnanda; Utami, Wiwik; Rahmawati, Rahmawati; Triyana, Kholish Fajri (Sean Institute, 2022)
Mental disorder is one of the four major health problems in developed and developing countries, including Indonesia. This study aimed to determine the role of spouses in caring for couples suffering from mental disorders in the Balen Public Health Center. The design in this research was descriptive with a survey approach. The respondents, all couples with mental disorders who are married in the Balen Public Health Center were 17 people, the sampling used is total sampling. Data processing starts with editing, coding, scoring, and tabulating. Of the 17 respondents, 8 respondents were deficient roles (47%). The conclusion is more than half of the spouses caring for couples suffering from mental disorders are deficient roles. Living partners of mentally disordered patients should improve support in daily patient care